Catch rate of juveniles Ethamatosa fimbriata, Sardinella maderensis, and Brachydeuterus auritus fishing in Freetown Peninsular - M. Sheriff; K. Kevin; T. N. Ndomahina; E. Taylor; O. K. M. Badr; K. J. Boateng; R. Sandi (Advances in Aquaculture and Fisheries Management, 2017)
We investigated the incidences of juvenile fishing according to fishing practices in Freetown peninsular. The industrial trawl fishing sector, despite its technology is not fully selective to avoid by-catch of juvenile fish, and artisanal fishing is so less for economic reasons. Ineffective enforcement of fishing regulations is a major cause to the catch of both targeted and non-targeted juvenile fish. We collected data on the quantity of juvenile fish and the daily duration of fishing trips in four landing sites over a two-week period Bernoulli random variables and properties of uniform distribution were used to analyze the data. Catch rates of juveniles Ethamatosa fimbriata, Sardinella maderensis, and Brachydeuterus auritus around the Freetown peninsular were 170.8, 212.4 and 194.60 kg per hour per day, respectively. This rate revealed that the current trend of juvenile fish landings is a threat to the sustainability of fishery capital, revenue, and biodiversity.